2021
DOI: 10.3389/fimmu.2021.666114
|View full text |Cite
|
Sign up to set email alerts
|

False Positive Results in SARS-CoV-2 Serological Tests for Samples From Patients With Chronic Inflammatory Diseases

Abstract: Patients with chronic inflammatory diseases are often treated with immunosuppressants and therefore are of particular concern during the SARS-CoV-2 pandemic. Serological tests will improve our understanding of the infection and immunity in this population, unless they tests give false positive results. The aim of this study was to evaluate the specificity of SARS-Cov-2 serological assays using samples from patients with chronic inflammatory diseases collected prior to April 2019, thus defined as negative. Samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…Presence of rheumatoid factor often challenges the specificity of immunoassays and is, in general, a common suspect of false positive tests. This was recently highlighted also for different immunoassays of serological SARS-CoV-2 testing in patients with chronic inflammatory diseases, whereof most of the investigated samples originated from patients with MS and RA (47). A subgroup of rituximab-treated SLE patients was included, but rheumatoid factor did not seem to have a major impact on the SARS-CoV-2 test results in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of rheumatoid factor often challenges the specificity of immunoassays and is, in general, a common suspect of false positive tests. This was recently highlighted also for different immunoassays of serological SARS-CoV-2 testing in patients with chronic inflammatory diseases, whereof most of the investigated samples originated from patients with MS and RA (47). A subgroup of rituximab-treated SLE patients was included, but rheumatoid factor did not seem to have a major impact on the SARS-CoV-2 test results in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to evaluate the specificity of SARS-CoV-2 antibody tests in a group of patients with autoimmune endocrine disorders. Kharlamova et al have recently shown a high false-positive rate when analyzing prepandemic samples of patients with chronic inflammatory diseases (multiple sclerosis, rheumatoid arthritis and systemic lupus erythematosus) using commercial serological tests [40]. Positive SARS-CoV-2 antibody test results in naive populations have previously been identified in stored prepandemic sera [13], and uninfected individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…For most part, enzyme-linked immunosorbent assay (ELISA), immunohistochemistry (IHC) and flow cytometer assays in particular are immunoassays routinely found in diagnostic laboratories. ELISA continues to be the gold standard for biomarker detection [117][118][119][120][121][122][123] because of its high precision, throughput, and sensitivity (In clinical diagnostic chemistry, a sensitive test refers to a test that will correctly identify almost all individuals who likely have a disease, and will rarely yield a false negative result. A specific test refers to a test that will almost always correctly rule out those who do not have a disease, and will rarely yield a false positive result [117].…”
Section: Limitations Of Existing Immunoassays Used In Clinical Diagnosticsmentioning
confidence: 99%
“…In analytical chemistry, sensitivity is the minimal detectable concentration of an analyte, expressed as the limit of detection (LoD), that can be accurately measured.). While the last two decades has seen tremendous innovation in ELISA technology, including automation with robotic workstations, improved microtiter plate readers, higher throughput well formats, and better antibody immobilization techniques, it has not been able to overcome for several reasons [119][120][121][122][123] limitations of diagnostic sensitivity [117] and specificity (Specificity is the ability to accurately assess a single analyte in the presence of components which may be expected to be present in the sample matrix, such as interferences. Similar to specificity, selectivity is the ability to accurately separate out and assess multiple components present in a sample mixture or matrix [119]).…”
Section: Limitations Of Existing Immunoassays Used In Clinical Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation